If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 49.5 = 0.5(9h) Remove parenthesis around (9h) 49.5 = 0.5 * 9h Multiply 0.5 * 9 49.5 = 4.5h Solving 49.5 = 4.5h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-4.5h' to each side of the equation. 49.5 + -4.5h = 4.5h + -4.5h Combine like terms: 4.5h + -4.5h = 0.0 49.5 + -4.5h = 0.0 Add '-49.5' to each side of the equation. 49.5 + -49.5 + -4.5h = 0.0 + -49.5 Combine like terms: 49.5 + -49.5 = 0.0 0.0 + -4.5h = 0.0 + -49.5 -4.5h = 0.0 + -49.5 Combine like terms: 0.0 + -49.5 = -49.5 -4.5h = -49.5 Divide each side by '-4.5'. h = 11 Simplifying h = 11
| 13-7+4*6= | | 4/7-x | | 300=2x+2(75) | | 13=-15+7p | | 60+30(4+x)+40+20x=470 | | 1-5x+4x=1 | | 6x+14x-7=5(4x+5) | | 7(2+6n)-n=178 | | 50=36.500.10m | | s-2s=5 | | 60+30x+60+30x+60+30x+60+30x+40+20x=470 | | 4(x+1)=3x+1+x | | 12x+11=9x+32 | | Bover-2=2.5 | | 5/4=5/x | | 8b+5=5b+9 | | -7(5a+5)-4=-5(7a-7) | | 2400+.018x=3246 | | X^3-9x^3= | | 3r+r=-2 | | 60+4(30x)+40+20x=470 | | 3n=5y(n+3) | | 2t+3t+8=3t-8 | | 8b+2=5b+4 | | -1/3+3 | | 5+2x=9+3X | | 8x+10+2x+1=7x-4 | | 5x+15x-3=4(5x+9) | | 9+2(x-7)=9-9(x-9) | | 4(60+30x)+40+20x=470 | | 6+1.50(x)=16.50 | | (4x-1)=-21 |